KOMPARASI UNDANG-UNDANG NOMOR 19 TAHUN 2019 DENGAN UNDANG-UNDANG NOMOR 30 TAHUN 2002 TERHADAP PENANGANAN KORUPSI - Mohammad Aldi Aliansyah; Bambang Waluyo (2021)
Indonesian corruption cases must be handled seriuosly, strictly and structured, considering the corruption case is one of the extra-ordinary crime in Indonesia, it needs requires obvious and purposeful legal basis with the purposes of optimizing the eradication of the corruption cases in Indonesia. The purpose of this research is to find out the comparison between law number 30 year 2002 about Commission to Eridicate Corruption and law number 19 year 2019 about second amendment law number 30 year 2002 about Commssion to Eridicate Corruption, then knowing the weaknesses in the implementation of law number 19 year 2019 with the improvement efforts. This research use the juridical-normative method. This research results in comparison of the article-by-article substance which is different between the two laws and fids a positives side as well as a solution to the weaknesses of law number 19 year 2019 about second amendment law number 30 year 2002 about Commssion to Eridicate Corruption. The conlusion in this research is that in addition to some weaknesses that have occured to the KPK after the implementation of law number 19 year 2019, there is also a good intentions, including to enforce the checks and balances function between KPK and the government.